Diet quality and cognitive performance of fishermen’s children in selected region of Terengganu, Malaysia: a cross-sectional study - Asma’ Ali; Nurul Nabilah Wagimin; Noor Salihah Zakaria; Khairil Shazmin Kamarudin; Hayati Mohd Yusof (Penerbit Universiti Kebangsaan Malaysia, 2020)
Fishermen’s children are vulnerable to food insecurity as well as undernourishment which may influence their cognitive performance. Nevertheless, there is a deficiency in terms of pertinent studies that have been done in Malaysia with regards to their diet quality and cognitive performance. Thus, this cross-sectional study was carried out to determine the diet quality and cognitive performance among 7 to 11 years-old fishermen’s children in Terengganu. A total of 95 respondents were selected and their dietary intake was attained through two days of 24 hr dietary recall and later analyzed using Nutritionist Pro application. The diet quality of the respondents was assessed using the Healthy Eating Index (HEI) while the cognitive performance was determined through 36-items of Raven’s Coloured Progressive Matrices. Results have shown that the respondents’ mean total HEI score was 50.41 ± 5.26 out of 100 points indicating poor diet quality. The level of cognitive performance is below average. Unfortunately, no significant association was found between the total HEI score and cognitive performance of the respondents (p=0.16). In the future, more studies need to be carried out on the relationship between diet quality and cognitive performance among these respondents for better understanding.